METHODICAL APPROACHES TO THE CREATION MOOC (EXPERIENCE LAC) - Nozdrina, Л.В. (Journal of Information Technologies in Education (ITE), 2016)
The article presents a number of problems, determining the current state of development of the domestic market of massive open online courses (MOOC). Considering the aim of the research, there is described national experience in this area, proposed and substantiated a number of the criteria and methodological approaches to the implementation of MOOC in higher education. The development of MOOC in the Lviv Academy of Commerce (LAC) is reviewed as example. The main factors which determine the success of this educational innovation in the domestic market and are put under the research are software platforms, multimedia software for creating video lectures, course structure and support the learning process. The results of study which have been analyzed in this course can have a positive impact on the functioning of the market MOOC in Ukrainian universities. The article focuses on finding the ways of improving the process of developing and implementing MOOC in higher education in the example of LAC where Web-center on the MOODLE platform is used for e-learning. Further research should focus on the development of institutional mechanisms to ensure the effective design, implementation and operation of the MOOC in the universities in Ukraine. Particular attention during learning in massive open online course should be aimed at improving the educational process and to strengthen student's motivation in MOOC. Experience of MOOC's development in LAC can be useful at creating similar courses at other institutions of higher education in the different platforms, both MOODLE, and on the others.